The Use of Photography in the Works of Ulrike Bollens (An Analytical Study) (Al-Academy, 2026)
This research, "The Employment of the Photographic Image in the Works of Ulrike Bollenz," addresses the artist's mechanism for using the image and how she works and employs it in her artwork. The research is determined by the title (The Employment of the Photographic Image in the Works of Ulrike Bollenz), which will be the general determinant of what will follow in the research path. The first chapter represents the methodological framework of the research, represented by the research problem that addressed shedding light on Ulrike's employment of the photographic image as a component in her artwork. The basic problem that this research the photographic image in the works of Ulrike Bollenz? The research also included the importance of being a cognitive study of the artistic process. The goal is to identify the use of the photograph in the works of Ulrike Bollenz, while the research was limited to the works of Ulrike, which relied on photographs as a basis in the process of producing them with various materials. The second chapter, which represented the theoretical framework, included two sections. The first section dealt with the impact of the photograph on the contemporary, while the second section talked about Ulrike Bollenz’s experience and style. The third chapter represented the research procedures, which were represented by (3) samples chosen intentionally based on the principle of the dominance of works in which the photograph was used.Among the most important results and conclusions:Adding value to the contemporary art scene, as it contributes to the development of photography and presents it as an independent art form. Her works are characterized by innovation, renewal, and imagination, as in work No. (3).Expanding the concept of photography. Ulrike Bollenz has gone beyond the traditional use of photography as a documentation tool and explored its artistic and aesthetic potential, contributing to the expansion of the concept of this art form